THE EFFECTIVENESS OF STRATEGY (4H) IN THE ACHIEVEMENT OF SCIENCE SUBJECT AMONG SECOND-GRADE INTERMEDIATE STUDENTS (American Journal of Interdisciplinary Research and Development, 2022)
The research aims to identify the strategy's effectiveness (4H) in achieving science subjects among students of the second intermediate grade. The research sample included two groups: the experimental group and the number of its students was (35), and the control group represented the other group, and the number of its students was (35). Intentionally, the researcher chose (Birir Intermediate School for Boys) from the research community represented by the middle schools affiliated to the Directorate of Education of Diyala Governorate / Baquba. The researcher adopted the experimental research method as a method for conducting his research, which includes one independent variable (the 4H strategy) and a dependent variable (the academic achievement). The researcher chose the experimental design to control the research variables, and before starting the experiment, the researcher rewarded the two research groups for the purpose of obtaining accurate results with the following variables: (chronological age calculated in months, previous achievement of students, and Raven's test of intelligence). After making parity between the two research groups, the researcher prepared the requirements for the application of plans, objectives and tests for the two research groups, and after completing the application of the experiment, the researcher applied his research tools to the two research groups. The researcher obtained data for the two research groups, as these data were processed statistically by t-test for two independent samples. The results showed that the students of the experimental group outperformed the students of the control group who studied according to the strategy (4H) in the achievement of science.